Interactions Between Sociology as A Discipline and Maritime Industries and Related Pursuits with Special Reference to The South China Sea Coast - Feng, Haiying; Squires, Victor R. (Advances in Social Sciences Research Journal, 2024)
Sociology is the systematic study of social behaviour and human groups. It focuses primarily on the influence of social relationships upon people’s attitudes and behaviour and on how societies are established and change. As a field of study, sociology has a very broad scope. For the purposes of this commentary, there will be a narrowing to embody the key interactions between people who live, work and recreate in the relatively narrow belt where the land meets the sea. Of course, the full extent of the interactions may be felt far away because rivers and canals link the hinterland with the coastal zone. This paper makes several contributions to the growing body of literature in the application of the tools used by sociologists to assess and evaluate the multi-faceted nature of the trends emerging from the growth and importance of maritime industries and related pursuits along the South China seacoast. Beginning with a very brief history ideas about the land/sea interactions and some analysis of examples of environmental determinism in practice.